Branching process descriptions of information cascades on Twitter. (20th March 2021) - Gleeson, James P; Onaga, Tomokatsu; Fennell, Peter; Cotter, James; Burke, Raymond; O'Sullivan, David J P
Abstract: A detailed analysis of Twitter-based information cascades is performed, and it is demonstrated that branching process hypotheses are approximately satisfied. Using a branching process framework, models of agent-to-agent transmission are compared to conclude that a limited attention model better reproduces the relevant characteristics of the data than the more common independent cascade model. Existing and new analytical results for branching processes are shown to match well to the important statistical characteristics of the empirical information cascades, thus demonstrating the power of branching process descriptions for understanding social information spreading.